Marketing Strategy Product Financing Mitraguna Benefits in Attracting Customer Interest in Shariah Bank Indonesia (BSI Kcp Kisaran) - Nadya Namora Hutabarat; Nurul Inayah; Nursantri Yanti (Dinasti Publisher, 2024)
The marketing strategy for Mitraguna Berkah financing products at Bank Syariah Indonesia (Bsi Kcp Kisaran) involves a marketing mix which includes Product, Price, Promotion and Place. The research methodology used in this research is the library research method which is supported by SWOT analysis. This research was carried out by collecting articles and scientific papers related to Mitra Guna financing products at Bank Syariah Indonesia KCP Kisaran and conducting a SWOT analysis to determine strengths, weaknesses, opportunities and threats in developing a marketing strategy plan. Mitra Guna's financing products have advantages such as fixed installments, take over from other banks, a maximum term of 15 years, and payroll and non-payroll financing. Bank Syariah Indonesia KCP Kisaran sets competitive margins and flexible financing ceilings. Strategic place in the center of Kisaran City with modern facilities. Promotion is carried out through outreach, brochures, sponsorship and advertising to increase public awareness.